Fractal Symmetry of Protein Interior - Banerji, Anirban; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Springer, 2013)
The essential question that fractal dimensions attempt to answer is about the scales in Nature. For a system as non-idealistic and complex as a protein, studying scale-invariance becomes particularly important. Fractal Symmetry of Protein Interior investigates the diverse facets of the various scales at which we describe protein biophysical and biochemical phenomena. Following a thorough introduction to fractal dimensions, fractal-dimension-based approaches, that have been employed to study protein interior biophysical properties, are described. The focus is on the question (3z(Bwhich scales are scale-invariant?(3y (BInvestigations related to scaling of biophysical and biochemical behaviors may one day help us to formulate a fundamental theory about protein biophysics; which, in turn, may help us to understand fundamental principles of proteins.s
Introduction: How did it all begin -- Brief history of fractal dimension -- Introduction to Fractals -- Misconceptions about fractals -- Studying Protein Interior with Fractal Dimension -- Why, at all, does one need fractal dimension to study protein interior -- Schools of protein interior fractal studies -- Results obtained with fractal dimension-based investigations -- Gaining new knowledge about protein interior with FD-based investigations -- New directions in FD-based protein interior research.
Keywords: Life sciences; Chemistry -- Mathematics; Biochemistry; Bioinformatics; Life Sciences; Protein Structure; Bioinformatics; Math. Applications in Chemistry; Protein Science